Scaffolds for whole organ tissue engineering: Construction and in vitro evaluation of a seamless, spherical and hollow collagen bladder construct with appendices. (1st October 2016) - Hoogenkamp, Henk R.; Pot, Michiel W.; Hafmans, Theo G.; Tiemessen, Dorien M.; Sun, Yi; Oosterwijk, Egbert; Feitz, Wout F.; Daamen, Willeke F.; van Kuppevelt, Toin H.
Graphical abstract: Abstract: The field of regenerative medicine has developed promising techniques to improve current neobladder strategies used for radical cystectomies or congenital anomalies. Scaffolds made from molecularly defined biomaterials are instrumental in the regeneration of tissues, but are generally confined to small flat patches and do not comprise the whole organ. We have developed a simple, one-step casting method to produce a seamless large hollow collagen-based scaffold, mimicking the shape of the whole bladder, and with integrated anastomotic sites for ureters and urethra. The hollow bladder scaffold is highly standardized, with uniform wall thickness and a unidirectional pore structure to facilitate cell infiltration in vivo . Human and porcine bladder urothelial and smooth muscle cells were able to attach to the scaffold and maintained their phenotype in vitro . The closed luminal side and the porous outside of the scaffold facilitated the formation of an urothelial lining and infiltration of smooth muscle cells, respectively. The cells aligned according to the provided scaffold template. The technology used is highly adjustable (shape, size, materials) and may be used as a starting point for research to an off-the-shelf medical device suitable for neobladders. Statement of Significance: In this study, we describe the development of a simple, one-step casting method to produce a seamless large hollow collagen-based scaffold mimicking the shape of the whole bladder with integrated anastomotic sites for ureters and urethra. The hollow bladder scaffold is highly standardized with uniform wall thickness and a unidirectional pore structure to facilitate cell infiltration in vivo . The closed luminal surface and the porous exterior of the scaffold facilitated the formation of a urothelial lining and infiltration of smooth muscle cells, respectively. The applied technology is highly adjustable (shape, size, materials) and can be the starting point for research to an off-the-shelf medical device suitable for neobladders.